The Role of Social Workers in Intervention with Women Victims of Sexual Harassments - Siti Ropiah; Budi Muhammad Taftazani (UIN Sunan Gunung Djati, 2022)
This article discusses about the problem of sexual harassment of women and the role of social workers in intervention with the victims. This theme was chosen because sexual harassment cases is still reported by various media and oraganizations. There are many kinds of sexual harassment problems experienced by women. In Indonesia, the victims are various, ranging from minors, teenagers and adults. Regardless of the patriarchal culture that exists in Indonesian society, women are entitled to protection from sexual acts. The impact of sexual harassment to women is not only physical but also psychological. The role of social workers is important in helping the victims to recover and fully functoning. This article was written based on literature studies from journals, books, and other documents related to sexual issues against women. The aim is to describe the role of social workers in dealing with women victims of sexual violence in accordance with the values, principles and the code of ethics of social workers.